Characteristics of Natural Fibre Composite using Sugarcane Bagasse for Body Part Fender Application - Abdul Basith Mahamod; Ismail, Norhasikin (Progress in Engineering Application and Technology, 2024)
Natural fibre composites have emerged as a promising alternative to traditional composite materials due to their eco-friendly nature, abundance, and desirable mechanical properties. This research focuses on the characterization of natural fibre composites utilizing sugarcane bagasse for body part fender application. Sugarcane bagasse, a byproduct of the sugar industry, presents an environmentally friendly and renewable source for natural fibres. The purpose of the tests is to analyses and determine mechanical properties of the material. Sugarcane bagasse was mixed with epoxy resin by three different percentage includes 10 %, 15 % and 20 % with ratio of epoxy resin: hardener was 3: 1. The specimen fabrication was doing in mould method which is with the mould 20 cm x 20 cm x 0.3 cm. using spray WD-40, for easier the sugarcane bagasse left from the mould. To make the specimen follow the ASTM dimension, hand grinder has been used to make the specimen. The detailed description starting with the specimen testing by ASTM D638 for tensile property and ASTM D790 for flexural property of the composite. Followed by specimen testing using ASTM D256 for the impact strength. From the experiment that has been conducted, the best percentage ratio is 20 %. Tensile strength and impact test at 20 % of sugarcane bagasse composite shows the best results with 13.92 MPa and 14.06 MPa respectively. These fibres may provide a noticeable improvement over 10 % and 15% ratio. By serving as reinforcement, the fibres strengthen the material’s structure without reducing its flexibility or making it brittle. The results demonstrate the potential of sugarcane bagasse composites as a suitable material for fender applications, offering desirable mechanical performance, reduced weight, and improved sustainability. The findings contribute to the advancement of natural fibre composites and provide insights into their application in automotive components, supporting the shift towards eco-friendly and lightweight materials in the automotive industry.